Effect of CoralـHydroxyapatite on bone healing in rabbits: a Radiographic Study - مهلوبي, أشرف; منذر أسعد; ازدهار عمار (Latakia University Journal -Medical Sciences Series, 2023)
A lot of grafts such as tri-calcium phosphate and non-bone grafts such as coral hydroxyapatite have been widely treated and recently used in orthopedic and dental surgery. The aim of this study was to compare radiologically the bone healing between hydroxyapatite prepared from coral in its burnt and dried models with spontaneous healing in bone defects with a diameter of 4 mm caused in the cortical bone of the left thigh of 4 male French rabbits weighing between 2 to 3 kg and aged 3 months. The burned model was implanted in the defect proximal to the femoral head, and the dried model was implanted in the distal defect while the median defect was left blank for comparison as spontaneous recovery.